PERAN KEPUASAN KERJA DALAM MEMEDIASI LINGKUNGAN KERJA, KOMPENSASI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN - Asih Niati; Yuni Diah Astuti; Teguh Ariefiantoro; Sulistyorini Sulistyorini (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine and analyze the effect of work environment, compensation, and workload on employee performance through job satisfaction as an intervening variabel for Kopi Nuri employees. This research is included in quantitative research because the approach used for research proposals, processes, hypotheses, fieldwork, data analysis, and conclusions up to writing uses aspects of measurement, calculation, formulas, and certainty of numerical data. The population in this study was all Kopi Nuri employees. While the sampel in this study was all Kopi Nuri employees, totaling 96 employees. These results indicate that the work environment has a positive and significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, the workload has a positive and significant effect on job satisfaction, the work environment has no significant effect on employee performance, compensation has no significant effect on employee performance, the workload has a positive and significant effect on performance, job satisfaction has a positive and significant effect on employee performance, work environment on employee performance mediated by job satisfaction, compensation on employee performance mediated by job satisfaction, the workload on employee performance mediated by job satisfaction.